Adopsi Nilai Moral Panton Aceh Dalam Focus Group Discussion sebagai Teknik Konseling Model KIPAS - Nasrizal Afriadi; Andi Mappiare-AT; Muslihati Muslihati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract:  This a research constructs of the focus group discussion with moral values in Panton Aceh to develop a new technique based on local culture, namely the Panton Aceh culture so that this a technique can be an effective and attractive to be used in the group counseling of setting service, so that guidance counseling teachers can helped to do group counseling services at the school. In the process of implementing focus group discussion technique containing Panton Aceh, following the model counseling steps KIPAS consisting of kabar gembira (good news), integrasi data, perencanaan kegiatan (plan of action), aktualiasi kegiatan  (actualization of plan), and selebrasi (celebrtion). The focus of this research is how the description of moral values that can be taken in Panton Aceh and how the construction of moral values in Panton Aceh that can be adopted becomes the content of the focus group discussion technique to modify student character.  The method used in this study is qualitative with the type of research Hemeneutika Gradamerian. The results of a research study, there are found that five moral values contained in Panton Aceh, namely humility, honesty, hard work, self control, and love to share. Next, the researcher constructs the implementation of focus group discussion techniques with moral values in the Panton Aceh.Abstrak: Penelitian ini mengonstruksikan teknik focus group discussion bermutan nilai moral dalam Panton Aceh untuk menggembangkan teknik baru yang berbasis budaya lokal yaitu budaya Panton Aceh supaya tenik ini dapat menjadi salah satu teknik yang efektif dan menarik untuk digunakan dalam setting layanan konseling kelompok, sehingga guru bimbingan konseling dapat terbantu untuk melakukan layanan konseling kelompok di sekolah. Dalam proses pelaksanaan teknik focus group discussion bermuatan Panton Aceh mengikuti langkah-langkah konseling model KIPAS yang terdiri dari kabar gembira, integrasi data, perencanaan kegiatan, aktualisasi kegiatan dan selebrasi. Fokus penelitian ini adalah bagaimanakah deskripsi nilai moral yang dapat diambil dalam Panton Aceh dan bagaimanakah konstruksi nilai moral dalam Panton Aceh yang dapat di adopsi menjadi isi teknik focus group discussion untuk memodifikasi karakter siswa. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan jenis penelitian Hemeneutika Gradamerian. Hasil kajian penelitian, peneliti menemukan ada lima nilai moral yang terdapat dalam Panton Aceh yaitu rendah hati, kejujuran, kerja keras, kontrol diri, dan gemar berbagi. Selanjutnya peneliti mengkonstruksi pelaksanaan teknik focus group discussion bermuatan nilai moral dalam Panton Aceh.